2020
DOI: 10.1177/2041731420930379
|View full text |Cite
|
Sign up to set email alerts
|

Bone regeneration capacities of alveolar bone mesenchymal stem cells sheet in rabbit calvarial bone defect

Abstract: Mesenchymal stem cells sheets have been verified as a promising non-scaffold strategy for bone regeneration. Alveolar bone marrow mesenchymal stem cells, derived from neural crest, have the character of easily obtained and strong multi-differential potential. However, the bone regenerative features of alveolar bone marrow mesenchymal stem cells sheets in the craniofacial region remain unclear. The purpose of the present study was to compare the osteogenic differentiation and bone defect repairment characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
0
28
0
2
Order By: Relevance
“…In addition to the collagen based artificial scaffolds or membranes, it is worthy to mention another promising type of scaffold, based more on the extracellular matrix as well as cells, named as “cell sheet” ( Chen et al, 2019 ; Lu et al, 2019 ). Cell sheet was efficaciously utilized in the regeneration of bone and periodontal ligament-like tissues as shown by recent works ( Dong et al, 2020 ; Liu Y. et al, 2020 ). Promising as it demonstrated to be, cell sheet manufacture requires high manipulation skills to ensure the quality control ( Chen et al, 2019 ), while the current artificial Col/PVA membrane offers the superiority in relatively easy manufacturing with controllability.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the collagen based artificial scaffolds or membranes, it is worthy to mention another promising type of scaffold, based more on the extracellular matrix as well as cells, named as “cell sheet” ( Chen et al, 2019 ; Lu et al, 2019 ). Cell sheet was efficaciously utilized in the regeneration of bone and periodontal ligament-like tissues as shown by recent works ( Dong et al, 2020 ; Liu Y. et al, 2020 ). Promising as it demonstrated to be, cell sheet manufacture requires high manipulation skills to ensure the quality control ( Chen et al, 2019 ), while the current artificial Col/PVA membrane offers the superiority in relatively easy manufacturing with controllability.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that adult manidular skeletal stem cells activated an embryonic NC cell‐like gene regulatory program that is dependent on the focal adhesion kinase pathway during distraction osteogenesis, 120 enabling these cells to acquire a more plastic, developmental state that aids in jaw bone regeneration. In addition, alveolar bone‐derived MSCs 121 display high osteogenic potential and promote ectopic bone formation in vivo, 122–125 providing a more accessible MSC source compared with the iliac crest.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that CHI3L1 is not synthesized in undifferentiated iliac MSCs [ 37 ], some undifferentiated MBMSCs synthesized and secreted CHI3L1 in this study. MBMSCs have lower chondrogenic and adipogenic differentiation capacity [ 9 ] and greater osteogenic differentiation capacity than iliac MSCs [ 38 , 39 ]. In addition, MBMSCs and iliac MSCs have been reported to have different gene expression according to DNA microarray analysis [ 40 ].…”
Section: Discussionmentioning
confidence: 99%